Using Anodonta Toothless as a Feed Additive on the Example of African Catfish Clarias Gariepinus - Kim, S. I. (American Journal of Biodiversity, 2024)
The effectiveness of using the meat of the toothless Anodonta as a feed additive was studied using the example of juvenile African catfish Clarias gariepinus. The difference in the weight gain of African catfish was established when feeding with regular carp feed, feed with the addition of minced meat made from the toothless, and feed consisting of 100% minced meat alone.